Organizational Culture Analysis and Management Information Systems in Educational Environments - Amirah , Cucu; Konidin, Toha (Journal of Management Economic and Financial, 2023)
Educational institutions as part of the organization certainly have differences when compared to other institutions, this reflects that educational institutions also have an organizational culture that is not the same as other institutions. Even other institutions that are both engaged in education will have their own organizational culture. All these differences occur due to differences in the viewpoints of leaders and members of the organization in determining the vision and mission and goals of the organization, besides that differences can also occur because of customers from different organizations. Organizational culture is a picture that distinguishes an organization from other organizations. Organizational culture is formed from habits, traditions and general ways of doing something that already exists in an organization is closely related to what has been done before and to the success rate of the organization with its efforts. Organizational culture is influenced by various elements, such as members of the organization who are at the forefront of managing the organization, organizational leaders with policies in determining a decision, internal factors determined by the activities or products of the organization, external factors such as the environment and society, and other influences that form a habit of the organization in solving problems to achieve goals organization.